Identifying Essential Components of School‐Linked Mental Health Services for Refugee and Immigrant Children: A Comparative Case Study. (28th November 2019) - McNeely, Clea A.; Sprecher, Katharine; Bates‐Fredi, Denise; Price, Olga Acosta; Allen, Chenoa D.
ABSTRACT: BACKGROUND: Foreign‐born children rarely use traditional school mental health services. Comprehensive programs that combine mental health services with academic, economic, and socioemotional supports reach more foreign‐born children and improve wellbeing. However, little practical guidance exists regarding how to best combine these diverse services. METHODS: To identify essential service components and their organization, we interviewed 92 parents, school staff, mental health providers, and community agency staff from 5 school‐linked mental health programs designed specifically to serve immigrant and refugee youth. RESULTS: Foreign‐born parents did not distinguish between academic, behavioral, and emotional help for their children; these western categorizations of functioning were not meaningful to them. Consequently, programs needed to combine 4 components, organized in a pyramid: family engagement, assistance with basic needs, assistance with adaptation to a new culture, and emotional and behavioral supports. Family engagement was the foundation upon which all other services depended. Assistance with economic and cultural stressors directly promoted emotional wellbeing and helped parents trust clinical mental health interventions. CONCLUSIONS: Specific strategies to implement the 4 essential components include home visits by program staff, a one‐stop parent center located in the school to help with basic needs, working with cultural brokers, and informed consent procedures that clearly explain recommended care without requiring immigrant and refugee parents to internalize western conceptualizations of psychopathology. Future evaluations should assess the cost and effectiveness of these strategies. These data are essential to advocate payment for these nonclinical services by traditional funding mechanisms.